Prevalence of Histologically Proven Acute Appendicitis and Incidental Carcinoid Tumour in the Practice of Surgical Pathology at BPKIHS - Upadhyaya, Paricha; Agarwal, C.S.; Karak, A.K.; Karki, S.; Pradhan, A.; Subba, T.N. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Appendicitis is the most common cause of acute abdominal pain requiring surgical intervention. Objectives: To determine the relative prevalence of histologically proven acute appendicitis in surgically resected specimens with clinical diagnosis of acute appendicitis and to find out the rate of occurrence of carcinoid tumour as an incidental histologic finding. Methods: Type of study- descriptive study Study unit- all gross specimens received in the department of pathology over a period of twenty months (1.1.2006 to 31.8.2007) Study sample- Histologic data on 515 appendicectomy samples (clinically diagnosed as appendicitis) of the total 7295 specimens received over a period of twenty months were retrieved from the archives of department of pathology, B. P. Koirala Institute of Health Sciences (BPKIHS). Exclusion criteria- appendectomy incidental to another surgical procedure. Results: Appendectomy specimens constituted 7.0% (n= 515; M:F 1.1:1) of all surgical pathologic specimens (n= 7295) at BPKIHS. Following is the breakup of histologic diagnosis: acute appendicitis with or without periappendicitis and gangrenous change (93.6%, n= 482), receding appendicitis (5.4%, n= 28), normal histology (1.0%, n= 5). Carcinoid tumours were detected incidentally in three cases (0.58%) out of the total number of 515 appendectomy specimens. Conclusion: Analysis of data revealed A relatively higher prevalence (6.99%) of histologically proven acute appendicitis in this Tertiary health care set up compared to similar data reported in the literature. Rate of occurrence (0.58%) of carcinoid tumour as incidental finding is similar to that reported in the literature.